2020
DOI: 10.1136/jitc-2019-000317
|View full text |Cite|
|
Sign up to set email alerts
|

Compound kushen injection relieves tumor-associated macrophage-mediated immunosuppression through TNFR1 and sensitizes hepatocellular carcinoma to sorafenib

Abstract: BackgroundThere is an urgent need for effective treatments for hepatocellular carcinoma (HCC). Immunotherapy is promising especially when combined with traditional therapies. This study aimed to investigate the immunomodulatory function of an approved Chinese medicine formula, compound kushen injection (CKI), and its anti-HCC efficiency in combination with low-dose sorafenib.MethodsGrowth of two murine HCC cells was evaluated in an orthotopic model, a subcutaneous model, two postsurgical recurrence model, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 102 publications
(78 citation statements)
references
References 46 publications
(48 reference statements)
1
71
0
Order By: Relevance
“…Clinical studies on non-small-cell lung carcinoma (NSCLC) ( 82 ), hepatocellular carcinoma ( 83 ), and ovarian cancer ( 84 ) use compound preparations, including classic traditional formula Xuefu Zhuyu decoction ( 82 ) and listed compound herbal medicine Shenqi Fuzheng injection ( 83 ). During in vitro and in vivo studies, apart from observing the effects on tumor cell proliferation, the related signaling pathways were explored, including the NF-κB and p38 MAPK signaling cascades mediated by TNFR1 in hepatocellular carcinoma cells (compound Kushen injection) ( 85 ) and the AKT pathway in gastric cancer and pancreatic cancer cells (Astragalus polysaccharide) ( 86 , 87 ). YIV-906, which is based on PHY906 ( 88 ), is a clinical observation drug that ensures > 90% consistency in product quality ( 89 ).…”
Section: Tcm Combined With Targeted Therapy or Immunotherapymentioning
confidence: 99%
“…Clinical studies on non-small-cell lung carcinoma (NSCLC) ( 82 ), hepatocellular carcinoma ( 83 ), and ovarian cancer ( 84 ) use compound preparations, including classic traditional formula Xuefu Zhuyu decoction ( 82 ) and listed compound herbal medicine Shenqi Fuzheng injection ( 83 ). During in vitro and in vivo studies, apart from observing the effects on tumor cell proliferation, the related signaling pathways were explored, including the NF-κB and p38 MAPK signaling cascades mediated by TNFR1 in hepatocellular carcinoma cells (compound Kushen injection) ( 85 ) and the AKT pathway in gastric cancer and pancreatic cancer cells (Astragalus polysaccharide) ( 86 , 87 ). YIV-906, which is based on PHY906 ( 88 ), is a clinical observation drug that ensures > 90% consistency in product quality ( 89 ).…”
Section: Tcm Combined With Targeted Therapy or Immunotherapymentioning
confidence: 99%
“…Currently, the curative treatment for early‐stage HCC patients includes liver resection, liver transplantation and local ablation 6 . It is noted that most HCC patients are diagnosed with advanced stage which means they cannot undertake those treatments because of dysfunction of liver 7 . Alternatively, only two targeted therapies sorafenib and lenvatinib have been approved by Food and Drug Administration as the standard frontline treatments for advanced HCC patients 8 .…”
Section: Introductionmentioning
confidence: 99%
“…6 It is noted that most HCC patients are diagnosed with advanced stage which means they cannot undertake those treatments because of dysfunction of liver. 7 Alternatively, only two targeted therapies sorafenib and lenvatinib have been approved by Food and Drug Administration as the standard frontline treatments for advanced HCC patients. 8 Similar to sorafenib, lenvatinib is an orally multi-targeted tyrosine kinase inhibitor that selectively inhibits vascular endothelial growth factor receptors (VEGFR), fibroblast growth factor receptors (FGFR), platelet-derived growth factor receptor α (PDGFRα), KIT and RET.…”
Section: Introductionmentioning
confidence: 99%
“…CKI mainly contains various anticancer ingredients, such as matrine and oxymatrine, which can inhibit the growth of tumour cells, overcome resistance to metastasis and multidrug resistance, and protect human immunity 8 . CKI has been utilized in clinical practice for decades to treat various solid tumour types, including liver cancer, breast cancer, gastric cancer, and other cancer types 8 , 9 . The analysis of medical data on 2,550 ESCA patients from 22 large-scale hospitals in China confirmed that CKI has been relatively widely used in the clinical treatment of ESCA of different severities 10 .…”
Section: Introductionmentioning
confidence: 99%